Effects of Bacillus thuringiensis subsp. aizawai GC91 (Agree WG) on R&D colonies of the buff-tailed bumblebee Bombus terrestris : (2.5 Part 2) - Sterk, Guido; Hannegraaf, Janna; Kolokytha, Paraskevi (Julius-Kühn-Archiv, 2020)
Bacillus thuringiensis subsp. aizawai, a widely used biological plant protection product, was tested on buff-tailed bumblebee Bombus terrestris, using an updated laboratory method on full standardized R&D colonies. The maximum field recommended concentration (MFRC) was applied through topical, oral pollen and oral sugar water treatment. Parameters such as survival of the mother queen and workers, formation of gynes, weight and volume of the colonies were recorded during the study, while the total number of formed workers/drones, the number of newborn gynes and queen brood were taken also at the end of the colonies’ life. For the evaluation of the results the data were calculated and categorized according to the IOBC side-effect classes, used for laboratory trials. According to the results, no toxic effect was recorded for all parameters taken from the bumblebee colonies when they were exposed to B. thuringiensis aizawai GC91.